I Want to Be Famous: A Screenplay About How Change and Chance Can Impact People’s Career - Fredi Setyawan; Ribut Basuki (Institute of Research and Community Outreach - Petra Christian University, 2025)
This thesis and screenplay aim to illustrate how change and chance can significantly impact people's careers, particularly for those actively pursuing their careers. The main character, Catherine, a public figure striving for greater fame, takes extreme measures to gain popularity. Initially, Catherine admires her idol, but she eventually begins copying her idol's content. Her underestimation for pivotal moments of change and chance, as highlighted by the Chaos Theory in Careers, leads her to seize fake opportunities while missing genuine positive ones. The story focuses on Catherine and her surroundings as she faces the consequences of underestimating change and chance in her career and her journey to recover from these mistakes. Through Catherine’s story, the screenplay demonstrates the importance of effectively managing change and chance for career advancement and long-term success.